On Grinbergs' differential geometry and finite fields - Zeps, Dainis (My University, 2019)
Emanuels Grinbergs, in his youth, during ten years, from 1933 until 1943, wrote three dissertations on one subject, namely, differential geometry [1, 2, 3]. We think that his work in this direction has been neglected for many years, and it is the last time to try to understand the significance of these works. Here, in this short article we touch only one aspect of this work, and compare and put together two approaches, one from thesis of Grinbergs [3], and another, of the author's, [5, 6], where we show close relation between both.
Keywords: differential geometry, osculating surface